1997
DOI: 10.1128/jvi.71.11.8774-8779.1997
|View full text |Cite
|
Sign up to set email alerts
|

A functional role for the conserved protonatable hairpins in the 5' untranslated region of turnip yellow mosaic virus RNA

Abstract: The 5 untranslated region (UTR) of the RNA of several tymoviruses contains conserved hairpins with protonatable internal loops, consisting of CC and C-A mismatches (K. Hellendoorn, P. J. A. Michiels, R. Buitenhuis, and C. W. A. Pleij, Nucleic Acids Res. 24, 4910-4917, 1996). Here, we present a functional analysis of the 5 UTR of turnip yellow mosaic virus (TYMV) RNA, which contains two protonatable hairpins with nearly identical internal loops. Mutations were introduced in an infectious cDNA clone, and T7 RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
5

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 21 publications
(26 reference statements)
0
11
0
5
Order By: Relevance
“…They seem to function as promoters for transcription and replication (Fodor et al, 1994(Fodor et al, , 1995Prehaud et al, 1997;Flick et al, 2002;Barr et al, 2003; Barr & Wertz, 2004; Kohl et al, 2006). Normally, these cis-acting sequences contain a few nucleotides that do not base pair and affect short loops that may have regulatory functions (Hellendoorn et al, 1997;Ito & Lai, 1997;Koev et al, 2002;Satyanarayana et al, 2002;Qi et al, 2003;Kohl et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…They seem to function as promoters for transcription and replication (Fodor et al, 1994(Fodor et al, , 1995Prehaud et al, 1997;Flick et al, 2002;Barr et al, 2003; Barr & Wertz, 2004; Kohl et al, 2006). Normally, these cis-acting sequences contain a few nucleotides that do not base pair and affect short loops that may have regulatory functions (Hellendoorn et al, 1997;Ito & Lai, 1997;Koev et al, 2002;Satyanarayana et al, 2002;Qi et al, 2003;Kohl et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although we have not looked for secondsite reversions that may also affect the fitness of progeny RNAs, our data indicate that preferred RNA sequence and structural elements of SL1 are selected for during PVX replication. Similar approaches have been used to identify functionally important structural features of several other viral RNAs, including HIV-1 (Berkhout and Klaver, 1995;Harrich et al, 1995), TCV (Carpenter et al, 1995;Carpenter and Simon, 1998), the bacteriophage MS2 (Olsthoorn et al, 1994), Q␤ (Klovins et al, 1998), turnip yellow mosaic virus (Hellendoorn et al, 1997), and cauliflower mosaic virus (Pooggin et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that PVX CP recognition sites have been altered by SL1 mutations, and revertant RNAs that restore CP binding may allow for efficient assembly of the genomic RNA and thus are selected for during encapsidation. Serial passage experiments with turnip yellow mosaic virus transcripts containing mutations in a 5Ј NTR stem-loop structure indicated that C-C or C-A mismatches were important for viral infection and appeared to function in viral packaging (Hellendoorn et al, 1997). For Rous sarcoma virus, Miller et al (1997) have shown that stem and loop elements within the U5-IR hairpin contribute to multiple biological roles, including the efficiency of reverse transcription and RNA packaging.…”
Section: Discussionmentioning
confidence: 99%
“…However, U-C mismatches, which occur in HP 2 and 3 of NeRNV RNA, have previously been found only in HP 2 of the 59-UTR of OYMV RNA (Hellendoorn et al, 1996b) and in the RNAs of the related Anagyris vein clearing virus, Plantago mottle virus and Scrophularia mottle virus (Koenig et al, 2005). For TYMV, it has been shown that the C-C (and also C-A) pairs in the internal loops of the hairpins of the 59-UTR form protonated base pairs at low pH and play an important role in the initiation of RNA encapsidation (Hellendoorn et al, 1997;Bink et al, 2002).…”
Section: The 5 § Utrmentioning
confidence: 99%